Washbasin hygiene trap: quantifying droplet inhalation risks during near-facial respiratory proximity behavior - Danting Luo; Mingrui Jiang; Xiaohong Zheng; Yuguo Li; Hua Qian (Building and Environment, 2026)

Bridging germplasm and mechanisms: screening for resistance and decoding defense strategies against rice gall midge (Orseolia oryzae Wood-Mason) in rice - Fugang Huang; Xiaolin Li; Zhe Jiang; Huayu Huang; Shahzad Ahmad; Shuolei Liao; Jieli Wei; Jiawang Peng; Xiaohui Zhong; Zuyu Liao; Jingying Li; Yifan Huang; et al. (Theoretical and Applied Genetics, 2026)

Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Multiplexed electrochemical biosensors: system-level design frameworks, signal decoding strategies and translational perspectives for food safety - Shuyu Zhou; Yingyu Wu; Yi Li; Wenjun Yu; Danting Yang (Food Research International, 2026)

Inhalation exposure and health risks of PM2.5-associated metals in a machinery plant: Probabilistic assessment and mask protection limits - Jianchao Ma; Fan Liu; Danting Luo; Xiaohong Zheng; Sujun Leng; Nianyong Zhou; Bingyuan Li; Hua Qian (Atmospheric Pollution Research, 2026)

Hypothalamic Oxytocin Neuronal Activation Induces Bipolar-Like Mood Changes in Mice in a Sex- and Dosage-Dependent Manner - Hong Tan; Shizhen Jin; Wenjin Lv; Lingyu Guo; Peiran Jiang; Yongjian Li; Mengjia Shi; Danting Wang; Yongcheng Wang; Aimin Bao (Neuroscience Bulletin, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Co-exposure to triclosan and polystyrene nanoplastics on neurodevelopmental toxicity and gut microbiota dysbiosis in zebrafish (Danio rerio) - Danting Wang; Junying Lan; Wentong Meng; Junping Liu; Ruixue Zhou; Chunxia Chen; Li Qin; Bin Tan; Chunyan Huang (Environmental Pollution, 2025)

Large-scale genomic and phenomic analyses of modern cultivars empower future rice breeding design - Xiaoding Ma; Hao Wang; Shen Yan; Chuanqing Zhou; Kunneng Zhou; Qiang Zhang; Maomao Li; Yaolong Yang; Danting Li; Peng Song; Cuifeng Tang; Leiyue Geng; et al. (Molecular Plant, 2025)

Exploring resistance mechanisms and identifying QTLs for brown planthopper in tropical and subtropical rice (Oryza sativa L.) germplasm - Fugang Huang; Zongqiong Zhang; Shuolei Liao; Juan Shen; Lanzhi Long; Jingying Li; Xiaohui Zhong; Zuyu Liao; Baiyi Lu; Fahuo Li; Zhe Jiang; Ling Cheng; et al. (Theoretical and Applied Genetics, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Seepage rate and uniformity of the stalk composite pipe for subsurface irrigation - Songmei Zai; Huanyu Wei; Xuemei Liu; Feng Wu; Linbao Liu; Danting Liu; Xin Li; Weiye Liu; Zaiyu Li (Irrigation and Drainage, 2025)
An orthogonal experiment with three factors and three levels was conducted to study the seepage rate and uniformity of stalk composite pipe (SCP) under subsurface SCP irrigation (SSI). Furthermore, to determine the best application mode for SSI, the pipeline length, irrigation volume and inner–outer diameter of the SCP were considered at a 0.4 m working pressure. The three levels corresponding to each factor were 20, 40 and 60 m; 30, 45 and 60 L m⁻¹; and 28–60, 40–80 and 50–100 mm, respectively. The results indicated that the seepage rate gradually decreased with increasing pipeline length. The pattern of the change in the seepage rate with irrigation volume was not obvious. There was a positive correlation between the seepage rate and the inner–outer diameter of the SCP. The irrigation uniformity coefficient, which was calculated based on the width of the surface wetting front, gradually decreased with increasing pipeline length. The impact patterns of irrigation volume and inner–outer diameter on irrigation uniformity were ambiguous. The seepage rate reached its maximum at the pipeline length, irrigation volume and inner–outer diameter, which were 20 m, 30 L m⁻¹ and 50–100 mm, respectively. There was the highest irrigation uniformity, with a pipeline length, irrigation volume and inner–outer diameter of the SCP of 20 m, 60 L m⁻¹ and 40–80 mm, respectively.

AI-based green technology implementation simulation for achieving carbon neutrality: exploring the role of subsidies and knowledge management - Jifan Ren; Qasir Abbas; Jafar Hussain; Danting Hu; Jimei Li (Environmental Science and Pollution Research, 2024)

The wall-associated kinase GWN1 controls grain weight and grain number in rice - Zhiqi Ma; Jinli Miao; Jianping Yu; Yinghua Pan; Danting Li; Peng Xu; Xingming Sun; Jinjie Li; Hongliang Zhang; Zichao Li; Zhanying Zhang (Theoretical and Applied Genetics, 2024)

Microbial community structure in a constructed wetland based on a recirculating aquaculture system: Exploring spatio-temporal variations and assembly mechanisms - Wenjie Tian; Qiufen Li; Zijun Luo; Chao Wu; Bo Sun; Danting Zhao; Saisai Chi; Zhengguo Cui; Ailing Xu; Zhiwen Song (Marine Environmental Research, 2024)

Explosive household spread of the SARS-CoV-2 Omicron variant in China in late 2022 - Nan Zhang; Yong Guo; Benjamin J. Cowling; Weiwei Huang; Wei Jia; Ao Li; Danting Luo; Donald K. Milton; Shengqi Wang; Hui-Ling Yen; Yinping Zhang; Yingxin Zhu; et al. (Building and Environment, 2024)

Comparing Mini and full-size electric vehicles in China: Evidence from user heterogeneity and satisfaction asymmetry - Shaoxuan Zhu; Danting Zhao; Yihao Li (Journal of Cleaner Production, 2024)

The application and development of electron microscopy for three-dimensional reconstruction in life science: a review - Jingjing Zhao; Xiaoping Yu; Xuping Shentu; Danting Li (Cell and Tissue Research, 2024)

Risk evaluation of venue types and human behaviors of COVID-19 outbreaks in public indoor environments: A systematic review and meta-analysis - Weiwei Huang; Caroline X. Gao; Danting Luo; Yong Wang; Xiaohong Zheng; Cong Liu; Ying Wang; Yuguo Li; Hua Qian (Environmental Pollution, 2024)

Early monitoring of pore wetting in membrane distillation using ultrasonic time-domain reflectometry (UTDR) - Hongting Wan; Xianhui Li; Yusen Luo; Danting Shi; Tengjing Gong; Alicia Kyoungjin An; Senlin Shao (Water Research, 2023)

The root-associated Fusarium isolated based on fungal community analysis improves phytoremediation efficiency of Ricinus communis L. in multi metal-contaminated soils - Huaxiong Yao; Wenguang Shi; Xing Wang; Junyan Li; Meiqi Chen; Jianbin Li; Danting Chen; Lin Zhou; Zujun Deng (Chemosphere, 2023)

Spread of flushing-generated fecal aerosols in a squat toilet cubicle: Implication for infection risk - Danting Luo; Jiayu Huang; Xiaohong Zheng; Fan Liu; Yuguo Li; Ying Wang; Hua Qian (Science of The Total Environment, 2023)

Identification of sheath blight QTL in a LaGrue x Oryza nivara rice advanced backcross population - Georgia C. Eizenga; Danting Li; Melissa H. Jia; Trevis D. Huggins; Aaron K. Jackson (Euphytica, 2022)

Hybrid analytical-numerical modelling of ground vibrations from moving loads in a tunnel embedded in the saturated soil - Zonghao Yuan; Danting Xu; Li Shi; Xiaodong Pan; Ben He; Minyun Hu; Yuanqiang Cai (European Journal of Environmental and Civil Engineering, 2022)

Genetic networks underlying salinity tolerance in wheat uncovered with genome-wide analyses and selective sweeps - Danting Shan; Mohsin Ali; Mohammed Shahid; Anjuman Arif; Muhammad Qandeel Waheed; Xianchun Xia; Richard Trethowan; Mark Tester; Jesse Poland; Francis C. Ogbonnaya; Awais Rasheed; Zhonghu He; et al. (Theoretical and Applied Genetics, 2022)

Interferon-γ enhances the immunosuppressive ability of canine bone marrow-derived mesenchymal stem cells by activating the TLR3-dependent IDO/kynurenine pathway - Jiaqiang Deng; Danting Li; Xiaoya Huang; Weiyao Li; Fangfang Zhao; Congwei Gu; Liuhong Shen; Suizhong Cao; Zhihua Ren; Zhicai Zuo; Junliang Deng; Shumin Yu (Molecular Biology Reports, 2022)

Spatial and Seasonal Variations in the Stable Isotope Values and Trophic Positions of Dominant Zooplankton Groups in Jiaozhou Bay, China - Zhixin Ke; Ruofei Li; Danting Chen; Chunyu Zhao; Yehui Tan (Frontiers in Marine Science, 2022)
The spatial and seasonal distributions of stable carbon and nitrogen isotopes (δ 13 C and δ 15 N) in dominant zooplankton groups were investigated in Jiaozhou Bay. Zooplankton δ 13 C values ranged from −22.89‰ to −15.86‰, and δ 15 N values ranged from 3.18‰ to 13.57‰, respectively. The δ 13 C and δ 15 N values generally followed the order of small zooplankton < large calanoids < small Sagitta < large Sagitta . Spatial distribution patterns of zooplankton δ 13 C and δ 15 N values varied in different seasons. Our results suggested that the spatial variation of δ 13 C was mainly controlled by terrigenous organic matter (OM) input and phytoplankton biomass, but water temperature may have played a key role in the seasonal variation of δ 13 C. In spring, the high phytoplankton biomass might increase the δ 13 C value of small zooplankton in the inner bay. During other seasons, the δ 13 C values of zooplankton generally increased from the inner bay to the outer bay, which might be associated with the influence of 13 C-depleted terrigenous OM carried by the river discharge. Small zooplankton stable isotope values were significantly correlated with that of particulate organic matter (POM). The influence of anthropogenic nutrient input on isotopic baseline can be cascaded to the zooplankton, and the effect might be weak at higher trophic levels. The Bayesian standard ellipse areas of dominant zooplankton groups were generally smallest in the winter, suggesting a narrow niche width during that time. The niche partition between small zooplankton, large calanoids, and Sagitta was most distinct in winter, and followed by summer. The relative trophic level of Sagitta ranged from 2.23 to 4.01, which generally declined from the inner bay to the outer bay during the spring, autumn, and winter seasons. High anthropogenic nutrient loading might reduce the difference in trophic niches among zooplankton groups. This study provided detailed information on the distribution of zooplankton δ 13 C and δ 15 N in a coastal bay, which will be useful for understanding the anthropogenic influence on the ecosystem structure and function.

Ribosomal ITS sequence-directed selection for endophytic Myrothecium strains antagonistic to Ralstonia solanacearum to control patchouli bacterial wilt - Wenguang Shi; Jiaqi Li; Huaxiong Yao; Jianbin Li; Meiqi Chen; Danting Chen; Yinghao Fu; Huarong Xie; Zujun Deng (BioControl, 2022)

Fine mapping of S32(t), a new gene causing hybrid embryo sac sterility in a Chinese landrace rice (Oryza sativa L.) - Danting Li; Liangming Chen; Ling Jiang; Susong Zhu; Zhigang Zhao; Shijia Liu; Ning Su; Huqu Zhai; Hiroshi Ikehashi; Jianmin Wan (Theoretical and Applied Genetics, 2007)